Assessment of U.S. firm-level climate change performance and strategy. (May 2016) - Yu, Yu; Wang, Derek D.; Li, Shanling; Shi, Qinfen
Abstract: Climate change is becoming an increasingly critical concern for human society. While there has been a great deal of research on climate change performance at the country/region level, our research focuses on the study of firm-level environmental efficiency as a proxy for firms' climate change management. Using a unique data set on U.S. S&P 500 firms for the period 2012–2013 and DEA slack-based models, we obtain firms' environmental efficiencies in six sectors. The results show significant performance dispersions both across and within the sectors. We highlight each sector's pros and cons in the environmental performance and propose guidelines for policy makers to further improve climate change performance. We also evaluate firms' operational performance and propose a unified performance measure by integrating operational and environmental efficiencies. Overall, we find there is no significant relationship between operational and environmental efficiencies in any of the six industrial sectors under study. The unified performance measures are more driven by the environmental efficiency than the operational efficiency. Highlights: U.S. firms have large variations in climate performance across/within the sectors. Relationship between operational and climate performances is not significant. The operational and climate performances can be captured in a unified measure.